2017
DOI: 10.18203/issn.2454-5929.ijohns20171213
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal teratocarcinosarcoma: is minimally invasive resection followed by adjuvant histology directed chemo-radiation a better alternative to radical excision? Case report

Abstract: <p class="abstract">Sinonasal teratocarcinosarcoma (SNTCS) is a rare higly malignant tumour occuring almost exclusively in the sinonasal tract. This aggressive tumour arising from the primitive embryonic or immature pluripotential cells of olfactory epithelium has high propencity for loco-regional recurrence and mortality. SNTCS generally presents with relatively benign symptoms like nasal obstruction and recurrent epistaxis in its early stage. In advance stage with orbital and intracranial spread other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…An institutional study has reported the use of neoadjuvant chemotherapy [12] and tailored chemotherapy [13] (depending upon the type of predominant histology in the postoperative specimen) to avoid extensive craniofacial resection and positive margins. These protocols may have theoretical advantage in the management of SNTCS, however, lack of larger studies may confound in validation of these management algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…An institutional study has reported the use of neoadjuvant chemotherapy [12] and tailored chemotherapy [13] (depending upon the type of predominant histology in the postoperative specimen) to avoid extensive craniofacial resection and positive margins. These protocols may have theoretical advantage in the management of SNTCS, however, lack of larger studies may confound in validation of these management algorithms.…”
Section: Discussionmentioning
confidence: 99%